ANALISIS KASUS PERCERAIAN PADA MASA PANDEMI COVID 19 DI PENGADILAN AGAMA JAKARTA SELATAN - Gita Wahyu Septiani (2022)
This study aims to provide an overview of the increase in divorce cases during the Covid-19 pandemic, and also explain the reasons for filing a divorce lawsuit during the Covid-19 pandemic at the South Jakarta Religious Court. In the research method used is the Normative Legal Research Method supported by interviews with judges and clerks at the South Jakarta Religious Court, using a sociological juridical approach where researchers come directly to the field to obtain legal data and build legal arguments regarding cases or events that occur in the field. collection by directly coming to the field to conduct interviews with related parties and collect data related to the research topic. The results of this study indicate that the most dominating reason for divorce during the Covid-19 pandemic at the South Jakarta Religious Court is the background of disputes and quarrels, while the rate of divorce cases in the South Jakarta Religious Court has decreased compared to before the Covid-19 pandemic. this is influenced by limited services and also the lockdown policy that is applied so that it affects the level of cases that enter during the Covid-19 pandemic.